Production Networks and Trade Patterns in East Asia: Regionalization or Globalization? - Prema-chandra Athukorala (Asian Development Bank (ADB), 2010)
This paper examines the implications of global production sharing for economic integration in East Asia, with emphasis on the behavior of trade flows in the wake of the 2008 global economic crisis. While trade in parts and components and final assembly within production networks ("network trade") has generally grown faster than total world trade in manufacturing, the degree of dependence of East Asia on this new form of international specialization is proportionately larger than elsewhere in the world. Network trade has certainly strengthened economic interdependence among countries in the region, with the People's Republic of China (PRC) playing a pivotal role as the premier center of final assembly. However, contrary to the popular belief, this has not lessened the dependence of the export dynamism of these countries on the global economy. The rise of global production sharing has strengthened the case for a global, rather than regional, approach to trade and investment policymaking.
hdl:11540/1945
Keywords: F10; F14; O53; 330; production sharing; trade patterns; East Asia; PRC